Monitoring and Assessment of Social and Behavioural Factors Associated with Dental Caries Experience among Adolescent School Children in Bengaluru City, India - Sushi Kadanakuppe; S. S. Hiremath (Highlights on Medicine and Medical Research Vol. 2, 2021)
Aim: To assess the influence of social and behavioural factors on dental caries experience among adolescent school children in Bengaluru city, India. Study Design: Cross sectional study. Place and Duration of the Study: Primary schools of Bengaluru City, between November 2012 and March 2013. Methodology: A cross sectional study was conducted on 11 year old 814 adolescents attending upper primary schools of Bengaluru city and their parents. Separate interview for adolescent students and parents was conducted on behavioural and social factors respectively. Dental caries was recorded according to WHO criteria using mouth mirrors and CPI probes under natural light. Statistical analysis included descriptive analysis, bivariate analysis using chi-square tests and t-tests. Later the variables were subjected to logistic regression analysis. Results: Dental caries experience of the adolescents studied was associated with social factors such as occupation of the mother (OR=1.9; 95% CI=1.3-2.3), presence of social support for mother during adulthood (OR=2.1; 95% CI=1.4-2.0), possession of television (TV)/computer at home (OR= 1.6; 95%=0.9-3.0); and behavioral factors such as adolescents who consume less than one serving of dairy/ legumes/eggs/meat or poultry per day (OR=1.8; 95% CI=0.14-1.32), those who consume sweet snacks >1times in a day (OR=1.42; 95% CI=0.82-1.83), parents giving snacks as reward to adolescents who accomplish their wishes showed to be strongly associated with dental caries experience of adolescents (OR=2.34; 95% CI=1.2-3.4) Influence of TV on snacking, tooth brushing frequency and not using fluoridated dentifrice were also shown to be significantly associated with dental caries experience. Conclusion: Social factors such as occupation of the mother and social support play an important role in shaping the more proximal behavioural habits such as snacking among 11 year old adolescents. These interactions ultimately influenced dental caries experience in this age group.